COMMENT ON: RADIOLOGICAL EVALUATION OF SINONASAL, INTRAORBITAL AND INTRACRANIAL EXTENSION OF MUCORMYCOSIS IN POST-COVID PATIENTS - Alizai, Hassam Nasir Khan; Pasha, Aainah (MNJ (Malang Neurology Journal), 2026)
This letter critiques the article by Kalekar et al. that evaluates the radiological features and extent of mucormycosis, a rare and serious fungal infection, in post-COVID patients using computed tomography (CT) and magnetic resonance imaging (MRI). The letter points out some major flaws and weaknesses in the article, such as the lack of a clear research question and hypothesis, the weak literature review and theoretical framework, the poor study design and methodology, and the superficial discussion and conclusion. The letter suggests some ways to improve the article, such as formulating a specific research question and hypothesis, conducting a comprehensive and critical literature review, describing and justifying the study design and methodology in detail, and discussing the implications and limitations of the study. The letter hopes that the critique will help the authors revise their article and make it more suitable for publication.